Pola Asuh Ibu Bekerja Dalam Mendidik Kemandirian Anak - Juherti Artimi Liu; Fitri Rofiyarti; Muchamad Arif (MOTORIC, 2022)
The parenting style of parents, especially the figure of mother, makes a major contribution to the independence of preschooler. The figure of a working mother has different challenges in training her child's independence because of the limited time she has with her child. This research focuses on the parenting style practiced by mother (EY) as a worker, namely a teacher at a private school in Surabaya for her 5-year-old child (GE) related to independence. The author uses a qualitative it is a case study method by conducting observations, interviews and documentation to see the independence and upbringing that is applied. The results showed that the parenting style adopted by mother (EY) as a working mother was authoritarian and democratic. This parenting style supports GE's development to become an independent child.